2017
DOI: 10.1021/acs.jafc.7b02607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Composition and Structure of Excipient Emulsion on the Bioaccessibility of Pesticide Residue in Agricultural Products

Abstract: The influence of co-ingestion of food emulsions with tomatoes on the bioaccessibility of a model pesticide (chlorpyrifos) was studied. Emulsions were fabricated with different oil contents (0-8%), lipid compositions (medium chain triglyceride (MCT) and corn oil), and particle diameters (d = 0.17 and 10 μm). The emulsions were then mixed with chlorpyrifos-contaminated tomato puree, and the mixtures were subjected to a simulated gastrointestinal tract (GIT) consisting of mouth, stomach, and small intestine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…In addition to these areas, pyrazole derivatives have been successfully used in many fields such as pharmacy, agriculture, electronic industry, etc. They are used in a wide variety of agriculture industry as pesticides and insecticides agents and as pharmaceutical designers in industrial fields such as pharmacy and also are used in the technology industries to optical properties . For example, polymers containing pyrazole group are too useful for optoelectronic devices such as light emitting diodes and transistors due to low band gap …”
Section: Introductionmentioning
confidence: 99%
“…In addition to these areas, pyrazole derivatives have been successfully used in many fields such as pharmacy, agriculture, electronic industry, etc. They are used in a wide variety of agriculture industry as pesticides and insecticides agents and as pharmaceutical designers in industrial fields such as pharmacy and also are used in the technology industries to optical properties . For example, polymers containing pyrazole group are too useful for optoelectronic devices such as light emitting diodes and transistors due to low band gap …”
Section: Introductionmentioning
confidence: 99%
“…Co-ingestion of emulsions with fruits and vegetables may therefore increase the bioavailability of undesirable pesticides, as well as any desirable nutraceuticals or vitamins. Indeed, in a previous study, we showed that oil-in-water emulsions could increase the bioaccessibility of hydrophobic pesticides on tomatoes . Moreover, we found that the efficacy of these emulsions at enhancing the bioaccessibility of the pesticides depended on their composition and structure.…”
Section: Introductionmentioning
confidence: 66%
“…The initial samples were passed through an in vitro simulated GIT model containing mouth, stomach, and small intestine phases, which has been described in detail in our previous study …”
Section: Methodsmentioning
confidence: 99%
“…Pesticides are commonly applied to fruits and vegetables during their growth and/or postharvest processing [20][21][22]. Previously, we demonstrated that mixing emulsions with tomatoes prior to digestion increased the bioaccessibility of chlorpyrifos, a non-polar pesticide [23]. As mentioned earlier, the digestion of oil droplets results in the production of mixed micelles within the gastrointestinal fluids, which solubilize any non-polar substances and carry them to the intestinal lining where they can be absorbed [10,11].…”
Section: Introductionmentioning
confidence: 80%
“…Three representative pesticides with different Log P values were examined: Bendiocarb (Log P = 1.7); parathion (Log P = 3.8); and chlorpyrifos (Log P = 5.3). The bioaccessibilities of the pesticides were measured after the samples were passed through a simulated gastrointestinal tract (GIT) [23]. Samples containing different amounts of oil droplets (0%, 4%, and 8%) were used to study the impact of the oil content of emulsion-based foods on pesticide bioaccessibility.…”
Section: Introductionmentioning
confidence: 99%